Nature's Chronicle: Geo-History and Artefacts Distribution in the Economic Patterns of Jayawarsa's Sovereignty (1186-1204 CE) - Sucahyo, Iqbal Rizki; Fatoni, Ahmad Fadhli; Hudiyanto, Reza; Lutfi, Ismail; Subekti, Arif; Purbaya, Ilzam Alzier Dianis; Faizzabi, Muhammad; Pratama, Ilham Putra; Rofi Uddin, Ahmad (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
Every culture develops based on geographical conditions where deepening with historical geography is needed to see the pattern of social life of the community. The social life of the ancient Javanese community formed a structured pattern based on economic, social, political, and religious aspects, one of which was in the Jayawarsa territory. Previous research was only limited to textual contexts such as inscriptions and kakawin so that it has not explored other factors such as geographical conditions and cultural heritage itself in the form of artifacts. This research examines the economic pattern and social life of the community in the reign of Sri Jayawarsa through Geohistorical approach with variables of History and Geography. Based on geographical, archaeological, and inscription interpretation data, this research reconstructs the community structure formed around Sirah Keteng site and Mruwak Village. The historical geography approach highlights human interaction with their environment in building spatial systems, economic patterns and cosmological orientation. The results also show the existence of a community pattern involving people's settlements, the territory of the clergy, and royal land grants. This study can enrich the understanding of the interrelation of spatial and cultural aspects in the development of the social and economic structure of the Jayawarsa period.